The Relationship of Occupational Health and Safety K3 to Employee Performance in the Workplace Systematic Review Prospective cohort study - Sri Wulan Bintang Khoirunnisa; Antonius Rino Vanchapo; Juandri Seprianto Tusi; Emanuel Suban Bala Lewar; Alpian Jayadi; Xie Guilin; Deng Jiao (Journal of World Future Medicine, Health and Nursing, 2023)
Occupational health and safety K3 ensures that people are not injured or become sick due to hazards in the workplace. ensuring that preventing the risk of frequent industrial accidents and diseases that cause the loss of workers' lives and or affect employee performance. K3 is a science that focuses on ensuring safety in the workplace. Occupational safety and health (K3) is defined as the science and application of technology regarding the prevention of work accidents and occupational diseases. By providing OSH protection, it is expected that workers can work safely, healthily and productively. Research purposes. To find out health and safety K3 on employee performance in the workplace. Method. Descriptive with observational cohort. Prospective. Results. Knowing the level of occupational health and safety K3 on employee performance at work. Conclusion. Therefore, it can be concluded that in occupational health and safety risks of OSH to improve the safety of health workers, which includes various occupational risk factors in the workplace, provide refresher training and routine induction training on OSH and use personal protective equipment (PPE). To ensure safety and health in the sector prioritizing the health of workers.